Application of electrical capacitance tomography in pharmaceutical fluidised beds – A review. (15th February 2021) - Wang, Haigang; Yang, Wuqiang
Abstract: Fluidised beds are commonly used in the pharmaceutical industry for granulation, drying and coating of powder or pellets. The product quality strongly depends on the operation of the fluidisation processes. As a pharmaceutical fluidised bed is a typical multi-scale gas-solids flow system, it is important to investigate the flow dynamics by advanced measurement tools for understanding, optimisation and control of the fluidisation processes. Electrical capacitance tomography (ECT) has been used for this purpose in the past two decades. This paper reviews the application of ECT in pharmaceutical fluidised beds. First, the principle of ECT is introduced, followed by typical applications related to pharmaceutical fluidised beds being reviewed, including the characteristics of flow dynamics in granulation, drying and coating processes. Second, diagnosis of process fault and control based on ECT are discussed. Third, ECT results are compared and validated with available data from other sensing modalities, e.g. pressure and optical probes. In the end of the paper, conclusions and the future application of ECT in pharmaceutical fluidised beds as well as key issues for application of ECT in the pharmaceutical industry are discussed, including re-engineering of ECT sensor design and further improvement in image reconstruction.